The influence of islamic bank and zakat on unemployment in urban and rural areas of Indonesia - Fajri, Mohammad Zen Nasrudin; Suminto, Ahmad; Rizqon, Abdul Latif (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
Unemployment in Indonesia has shown a downward trend in the last decade which is associated with the positive growth of Islamic banks and zakat in Indonesia. This research aims to reveal the impact of Islamic bank performance on unemployment in Indonesia at a national level, in urban and rural areas. It also aims to find out the impact of zakat performance on those groups of unemployment. ARDL method is used to analyze data between 2007 and 2022. The results of the findings show that the zakat collection positively affects national unemployment, urban unemployment, and rural unemployment in Indonesia in the long run. However, in the short run, it only increases urban unemployment. Meanwhile, Islamic bank financing significantly reduces national unemployment and urban unemployment in the short run but it has no impact on rural unemployment. In the long run, Islamic bank financing does not affect all kinds of unemployment.Keywords: Islamic bank, zakat, unemployment, urban, rural.